Islamic Values as a Deepening Catalyst in Building Disciplinary Culture through Instructional Leadership at Senior High School - Istikomah Istikomah; Fatma Nurmulia; Rika Sa'diyah; Nurul Ain Norman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study investigates how the instructional leadership of the principal at SMA Muhammadiyah 4 Depok constructs a disciplinary culture that generates graduates who excel intellectually, morally, and spiritually. Existing research on Islamic secondary schools rarely integrates instructional leadership theory with organizational culture analysis, and no study has explicitly examined how Islamic values deepen disciplinary culture beyond normative administrative control. Employing a qualitative single case study design following Yin, data were collected through semi structured interviews with ten purposively selected informants, non-participant field observations, and systematic document analysis. Two complementary theoretical frameworks guided the analysis: 1) Hallinger and Murphy’s Principal Instructional Management Rating Scale (PIMRS), specifically Dimension Three on creating a positive learning climate, and 2) Schein’s three layer Organizational Culture model comprising artefacts, espoused values, and basic underlying assumptions. Findings reveal that the principal comprehensively enacts all five PIMRS Dimension Three functions in a mutually reinforcing manner. Critically, through Schein’s analytical lens, disciplinary culture has penetrated to the deepest layer of basic assumptions, where discipline is internalized as an expression of Islamic faith, an Islamic cadre identity, and a component of holistic intelligence. The study contributes a novel integrated model demonstrating that Islamic values operate as a cultural deepening catalyst that accelerates value internalization beyond the reach of external control a mechanism not previously identified in the literature. Practically, this model offers Islamic school leaders a replicable framework for embedding discipline as a core Islamic value, designing merit based recognition systems, leveraging digital accountability, and integrating spiritual development into teacher professionalism programs.